L’auteur de doublage, adaptateur du texte filmique : un traducteur-dialoguiste au service de la multimodalité - Brisset, Frédérique (Studia Romanica Posnaniensia, 2019)
As moving, multimodal texts, devised to be embodied by an actor, cinematic texts combine many characteristics which make them difficult to grasp, and which give their translation a high level of complexity. Those are paramount in dubbing. Combined to the technical and linguistic issues at stake, the process induces a singular relation between the audiovisual translators and the verbal material of the dialogues. This is often solved through a functionalist approach, seeking a dynamic equivalence which takes into account the many components of the filmic text, for the benefit of the dubbing actors and, eventually, the foreign audience. After addressing the questions of the authorial and legal status of the translators as scriptwriters, this article draws on several examples taken from different American cinematic genres to illustrate the various aspects of this relation in the French audiovisual translation context.